Pengembangan Sistem Perancangan Karir Sicakar Berbasis Web - Sri Puji Utami; Sari Zakiah Akmal; Della Piana (Jurnal Inovtek Polbeng Seri Informatika, 2018)
Careers are closely related to work, but have a broader meaning than work. Careers can be achieved through work that is planned and developed optimally and appropriately, but work can not always support career achievement. Career planning and development, usually done by psychologists by way of counseling or by giving a questionnaire. Questionnaire is a list of questions about the nature of the individual and or some approach using methods that have been adapted to the habits of the community where he lived. In processing the questionnaire the calculations are still done manually so it takes a long time to get the results. In this study developed Sistem Perencanaan Karir (SICAKAR) by using methods - methods that have been adapted to the habits of the people of Indonesia.